2005
DOI: 10.1016/j.jsv.2004.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical systems approach to fatigue damage identification

Abstract: In this paper, we present a dynamical systems approach to material damage identification. This methodology does not depend on knowledge of the particular damage physics of material fatigue. Instead, it provides experimental means to determine what are practically observable and observed facts of damage accumulation, thus making it possible to develop or experimentally verify appropriate damage evolution laws. A concept of phase space warping is used to develop new damage tracking feature vectors from measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
(43 reference statements)
3
31
0
1
Order By: Relevance
“…The next two SOCs show high sensitivity to the dramatic changes at the end of the experiment, but have clear discontinuities and considerably more noise. As in Chelidze & Liu (2005), the beam was made of carbon steel. The Paris law of macroscopic crack growth for this material stipulates a quadratic form of slow-time equation in equation (3.1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The next two SOCs show high sensitivity to the dramatic changes at the end of the experiment, but have clear discontinuities and considerably more noise. As in Chelidze & Liu (2005), the beam was made of carbon steel. The Paris law of macroscopic crack growth for this material stipulates a quadratic form of slow-time equation in equation (3.1).…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that the algorithm can identify two-dimensional damage trajectory's phase space (Chelidze 2004;Chelidze & Liu 2005). In addition to the changes in the slow-time variables, these systems were observed to go through bifurcations in their fast-time behaviour.…”
Section: Theorymentioning
confidence: 96%
See 1 more Smart Citation
“…t ∈ T ⊂ R is time, overdots denote time differentiation, 0 < 1 is a small rate constant defining the time scale separation. This formulation is relevant to tracking and identifying damage processes as discussed in [5]. It is assumed that the variable φ changes slowly.…”
Section: Reconstructing Slowly Drifting Variablesmentioning
confidence: 99%
“…SOD can be thought of as an extension of POD [14][15][16][17][18][19][20][21]. In addition to considering spatial (i.e., statistical) characteristics of the data set as in POD, SOD considers temporal (i.e., dynamical) characteristics of the data set as well.…”
Section: Introductionmentioning
confidence: 99%